Factors affecting lifelong learning of the elderly in Lampang Province - Wongyos, Nittaya; Sirisugandha, Thanakorn; Kamwass, Supunnee (Journal of Graduate MCU KhonKaen Campus, 2025)
The objectives of this research were (1) to examine the levels of motivation and needs, physical and mental health, social support, and lifelong learning among the elderly in Lampang Province, and (2) to investigate the factors influencing lifelong learning. The sample comprised 380 elderly participants, and data were collected via questionnaires. Descriptive statistics and multiple regression analysis (Enter method) were employed. The findings revealed that physical and mental health had the highest mean score, followed by motivation and needs, while social support and lifelong learning were at high levels. The multiple regression analysis indicated that physical and mental health was the strongest predictor of lifelong learning (β = 0.522, p < .01), followed by motivation and needs (β = 0.326, p < .01) and social support (β = 0.115, p < .01). The regression model explained 17.80% of the variance (R² = 0.178) in lifelong learning among the elderly in Lampang Province.